SIFAT FINAL DAN MENGIKAT PUTUSAN DEWAN KEHORMATAN PENYELENGGARA PEMILU (DKPP) DALAM MEWUJUDKAN KEADILAN ELEKTORAL (ELAKTORAL JUSTICE) DAN BUDAYA DEMOKRASI - I Gede Druvananda Abhiseka; I Made Adi Widnyana (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Elections are one of the mechanisms for the transition of power that was born at the same time as democracy. in Indonesia there are three institutions involved in holding general elections (elections), namely KPU, Bawaslu, and DKPP, DKPP officially becomes a state institution in the realm of upholding the ethics of holding elections. The presence of this DKPP is a solution to problems regarding integrity and credibility of election organizers, as well DKPP can be said that this institution is an institution that performs mixed functions (mix-function), namely administrative, regulatory, and punitive functions. DKPP in the decision as referred to in Article 458 paragraph (10) is final and binding. So from the above the presence of the DKPP is very important, and the presence of the DKPP is a solution to problems regarding the integrity and credibility of election organizers, because elections with integrity are still a serious problem, especially in Indonesia. The purpose of this research is to find out and show a paradigm as well as new hopes for the legal system and constitutional law in the future, especially in electoral law. The research method that the author uses is descriptive qualitative, that is, writes down by deciphering the extent to which the development of the findings that the author is doing for that there is data that the author will collect, such as primary and secondary data. The results of this study indicate that one of the DKPP's powers lies in the decisions made by the DKPP namely